The Effect of Accounting Knowledge on Student Investment Intention with Fear of Missing Out (FoMO) as Moderation: Supporting SDG 4 - Dewi Kusuma Wardani; Suyanto Suyanto; Tiara Pratama Putri; Devian Alestu Damayanti; Vivi Septiani; Maria Yasinta Sarina Putri (Journal of Current Studies in SDGs, 2027)
Objective: To examine the effect of accounting knowledge on student investment intention and investigate the moderating role of Fear of Missing Out (FoMO) in strengthening the relationship between accounting knowledge and investment intention. This study contributes to the achievement of Sustainable Development Goals (SDGs), particularly SDG 4 through improving financial education and SDG 8 by encouraging responsible economic participation among young generations. Method: A quantitative research approach using primary data collected through questionnaires distributed to university students in Indonesia. The sample consists of 205 active students from economics faculties across several Indonesian universities. Data analysis was conducted using simple regression analysis to examine the direct effect of accounting knowledge on investment intention and moderation analysis using the absolute difference value test to examine the role of FoMO as a moderating variable.  Results:  The results indicate that accounting knowledge has a positive and significant effect on student investment intention. Furthermore, FoMO strengthens the positive relationship between accounting knowledge and investment intention, indicating that students with stronger accounting knowledge and higher awareness of investment opportunities tend to demonstrate greater investment intention. Novelty: The study extends previous investment intention research by introducing FoMO as a moderating variable in the relationship between accounting knowledge and investment intention. The findings highlight the importance of integrating accounting education and behavioral factors to encourage informed investment decisions among young investors, supporting sustainable financial literacy development.